2019
DOI: 10.1590/s1677-5538.ibju.2018.0564
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PI-RADS v2 on indication of prostate biopsy

Abstract: Objectives:To identify the group of patients who could safely avoid prostate biopsy based on the findings of multiparametric prostate resonance imaging (MRmp), parameterized with PI-RADS v2, using prostate biopsy as reference test and to assess the sensitivity and specificity of mpMR in identifying clinically significant prostate cancer using prostate biopsy as a reference test.Patients and Methods:Three hundred and forty two patients with suspected prostate cancer were evaluated with mpMR and prostate biopsy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Conversely, three retrospective studies reported NPVs ranging from 96.5% to 99% [24,25,28]. However, although all three studies included a significant number of men with non-suspicious mpMRIs (114, 100 and 201, respectively), the NPVs described were likely driven by the majority of patients with previous negative biopsies and the very low rate of significant cancers diagnosed among them.…”
Section: Mixed Populationsmentioning
confidence: 95%
“…Conversely, three retrospective studies reported NPVs ranging from 96.5% to 99% [24,25,28]. However, although all three studies included a significant number of men with non-suspicious mpMRIs (114, 100 and 201, respectively), the NPVs described were likely driven by the majority of patients with previous negative biopsies and the very low rate of significant cancers diagnosed among them.…”
Section: Mixed Populationsmentioning
confidence: 95%
“…The results were similar to previously published studies in literature. [ 9 13 14 ] Another significant aspect of our results was that all patients with clinically significant tumors had PI-RADS v2 3–5 score, signifying that PI-RADS v2 score 3 can be considered as cutoff value for biopsy. Similar conclusions were also derived by Rozas et al .…”
Section: Discussionmentioning
confidence: 73%
“…Similar conclusions were also derived by Rozas et al . [ 9 ] in their study. Both the false-negative tumors in our study were low-grade cancers with Gleason score 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 Multiparameter magnetic resonance imaging (mpMRI) has been increasingly used to diagnose patients with PCa. 7 , 8 In 2012, the European Society of Urogenital Radiology (ESUR) established a series of guidelines for the interpretation of mpMRI images using a structured reporting scheme called Prostate Imaging Reporting and Data System (PIRADS). 9 In 2015, the American College of Radiologists, EUSR and the AdMeTech Foundation improved and updated PIRADS to version 2 (PIRADS V2).…”
Section: Introductionmentioning
confidence: 99%